Frequency of pregnancy induced hypertension and its association with elevated serum beta human chorionic gonadotropin levels during mid trimester of pregnancy - Habib, Saman; Haq, Aqsa Ikram ul; Bashir, Shama; Sadiq, Nadia; Majeed, Noreen; Waheed, Nabeela (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the frequency of PIH amongst elevated beta-hCG levels and non-elevated beta-hCG in the mid-trimester of pregnancy. Materials and Methods: It was Descriptive case series conducted for six months (02-12-2019 to 02-06-2020) in OPD of Gynae Unit-II, Holy Family Hospital, Rawalpindi. A total of one hundred and twenty-two (n=122) normotensive pregnant females at 13-20 weeks gestational age and 18-35 years of maternal age were selected in this study after informed consent from every patient. The frequency of PIH in patients with elevated serum beta-hCG was measured. Data were analyzed using SPSS version 20. Effect modifiers were controlled by stratification. A p-value of ≤ 0.05 was considered significant. Results: Mean beta-hCG levels in the total study population were found to be 7305.09±3900.64 IU/mL. Median b-hCG levels in our study population were noted as 6936.15 IU/mL. Pregnancy-induced hypertension was found positive in 16 (13.1%) patients. Raised beta-hCG levels were present in 10 (8.2%) patients. The frequency of PIH in raised beta-HCG levels was found in 7/10 (70%) of patients. We found a statistically significant (p-value ≤ 0.05) difference in the frequency of PIH among patients with elevated and not-elevated beta-hCG levels. Conclusion: It is evident from my study that patients with raised levels of serum β-hCG during mid-trimester pregnancy are at increased risk to develop hypertensive disorders of pregnancy. We further elaborated that there is a statistically significant difference in various effect modifiers such as maternal age, gestational age, residential status, and BMI for developing PIH among patients with elevated and non-elevated beta-hCG levels.